2022
DOI: 10.3390/ijms23158300
|View full text |Cite
|
Sign up to set email alerts
|

Counteraction of Myocardial Ferritin Heavy Chain Deficiency by Heme Oxygenase-1

Abstract: Given the abundance of heme proteins (cytochromes) in the mitochondrion, it is evident that a meticulously orchestrated iron metabolism is essential for cardiac health. Here, we examined the functional significance of myocardial ferritin heavy chain (FtH) in a model of acute myocardial infarction. We report that FtH deletion did not alter either the mitochondrial regulatory and surveillance pathways (fission and fusion) or mitochondrial bioenergetics in response to injury. Furthermore, deletion of myocardial F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Deletion of myocardial FHC was responsible for compensatory upregulation of some iron resistance genes comprising heme oxygenase ( HO-1 ). During this process, HO-1 induced solute carrier family 7 member 11 ( SLC7A11 ) overexpression, protected the heart from ischemia reperfusion-mediated ferroptosis, and safeguarded mitochondrial function ( Machado et al, 2022 ). Cheng et al reported stimulated HO-1 in rat glomerular mesangial cells to enhance their resistance to hydrogen peroxide.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of myocardial FHC was responsible for compensatory upregulation of some iron resistance genes comprising heme oxygenase ( HO-1 ). During this process, HO-1 induced solute carrier family 7 member 11 ( SLC7A11 ) overexpression, protected the heart from ischemia reperfusion-mediated ferroptosis, and safeguarded mitochondrial function ( Machado et al, 2022 ). Cheng et al reported stimulated HO-1 in rat glomerular mesangial cells to enhance their resistance to hydrogen peroxide.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Ma et al [ 132 ] reported that the expression of antioxidant sirtuin 1 (SIRT1) in the heart tissue was repressed after I/R damage, and SIRT1 overexpression was shown to lower the extent of I/R injury-related ferroptotic cell death via p53/SLC7A11 axis. Machado et al [ 133 ] reported that during cardiac I/R injury, ferritin shortage activates the synthesis of many antiferroptotic proteins, including HO-1. In turn, HO-1 upregulation leads to SLC7A11 induction and hence to GSH generation which reduces ferroptosis and preserves heart function.…”
Section: Ferroptosis and Cvdsmentioning
confidence: 99%
“…In turn, HO-1 upregulation leads to SLC7A11 induction and hence to GSH generation which reduces ferroptosis and preserves heart function. Nevertheless, HO-1 upregulation may be a double-edged sword since it causes heme degradation and the release of Fe 2+ which promotes ferroptosis [ 133 ]. Finally, it has to be noted that ubiquitination and some non-coding RNAs have also been shown to play a role in ferroptosis induced by I/R injury [ 134 ].…”
Section: Ferroptosis and Cvdsmentioning
confidence: 99%
“…, Baba et al (2018, showed that inducing ferroptosis in cardiomyocytes significantly increased cell death and ROS production, which was alleviated by treatment with Ferrostatin-1, an ROS scavenger. Machado et al (2022), in 2022 examined if FHC deletion in cardiomyocytes altered mitochondrial dynamics and cardiac function. Interestingly, they found that deletion of FHC did not affect mitochondrial or overall cardiac function, but rather the expression of genes related to glutathione metabolism, including SLC7a11 and heme oxygenase 1 (HO-1).…”
Section: Cellular Impacts Of Iron Dysregulation In Cardiomyocytesmentioning
confidence: 99%